Analysis of Road Widening Reviewed From The Service Level of Kedung Jajang – Ranuyoso, Lumajang - Rizal Chrisna Ardyansyah; Dr. Atik Wahyuni (Journal of World Conference (JWC), 2022)
Indonesia is a developing country that has various problems, one of which is congestion. Congestion occurs because of the high population, population mobility and poor road facilities. The congestion that occurs in Lumajang Regency is on the Kedungjajang - Ranuyoso road. Congestion is caused by the high mobility of the population to work, and the high side barriers. The purpose of this study was to determine the cause of congestion, the amount of road capacity, and the comparison of the level of road service before and after widening the Kedungjajang - Ranuyoso road. Data collection uses measurement data analysis techniques and documentation that was carried out before and after the widening of the Kedungjajang - Ranuyoso road section. The results showed that the cause of congestion that occurred on Jalan Kedungjajang-Ranuyoso Lumajang was the lack of effective road width, the amount of traffic capacity of the Kedungjajang-Ranuyoso Lumajang road before the widening of the road was 2,291 smp/jam, the amount of traffic capacity of the Kedungjajang-Ranuyoso road Lumajang after road widening is 3069.94 smp/jam, changes in the level of service for the Kedungjajang-Ranuyoso road Lumajang before and after road widening have increased by 2 levels, which originally had a road service level value of "E" to "C" which means the condition the original flow before road widening was unstable current, the speed sometimes stopped, demand was approaching